3(-x+9)=8-6x

Simple and best practice solution for 3(-x+9)=8-6x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(-x+9)=8-6x equation:



3(-x+9)=8-6x
We move all terms to the left:
3(-x+9)-(8-6x)=0
We add all the numbers together, and all the variables
3(-1x+9)-(-6x+8)=0
We multiply parentheses
-3x-(-6x+8)+27=0
We get rid of parentheses
-3x+6x-8+27=0
We add all the numbers together, and all the variables
3x+19=0
We move all terms containing x to the left, all other terms to the right
3x=-19
x=-19/3
x=-6+1/3

See similar equations:

| 3x+2x+5=8x-13 | | 20=6y+8 | | x+(x+5)+2(x+5)=35 | | 4x+(3x+1)=6-2(x-1) | | 6+-3m=15 | | 30=2(u+6)-5 | | 7x+6=x+6 | | -6=-8w+5(w-3) | | 10x+4=8x+24 | | 4a=4-20 | | 10x5=20-20x | | w+14=√256 | | 4x^-56x+196=0 | | 6.5=8.9-0.8x | | 164°-x=x+60° | | -6=-8w+5(w-3 | | 4(2x+7)-7=13 | | 2=3*2x | | 4x+5x-8=10 | | -5t=8-5 | | 5u/4-24/4=0 | | -8(n+8)=-112 | | (5u-24)/4=0 | | 10=-6x+4(x+3) | | 10g-5=-5+10g | | 2x-10°=74° | | 8(x+2)-14=26 | | 4-2x+6x=16 | | 6x^2+1=487 | | 2|t-6|=22 | | -3(x+2.8)=23.4 | | 0.54=0.36k |

Equations solver categories